THE SILK ROAD AS A MIRROR OF INTANGIBLE CULTURAL HERITAGE (Archive of Conferences, 2021)
The following article is written about the Great Silk Road and its importance to the world and the countries that are located there. The article demonstrates the intangible cultural heritage as a mirror of itself. The following written text demonstrates the history, the years of its usage widely and its importance in nowadays.